Perilaku Hidup Konsumtif Remaja Muslim di Pilar Coffee Bukittinggi - Akdila Bulanov (Tamaddun, 2019)
Currently among Muslim youth there has been a shift in shopping behavior to coffeshop. Muslim youths are looking for excessive entertainment because they tend to follow models of today's development. The presence of the coffeshop has an impact on the consumptive behavior of Muslim teenagers. Based on the participation observation that there is a relationship between the existence of coffeshop to consumptive behavior of Muslim teenagers. Based on the results of the analysis of Islamic economic view that the behavior of consumptive Muslim teenagers is not in accordance with the behavior in consumption in Islamic economics which refers to the three basic principles of consumption that has been outlined by Islam is kosher consumption, consumption of sacred goods and not excessive. Consumption of Muslim teenagers is included in the category of consumptive behavior.